The study of CD14+HLA-DR-/low myeloid-drived suppressor cell (MDSC) in peripheral blood of peripheral T-cell lymphoma patients and its biological function - Du, J.; Sun, X.; Song, Y (Cellular and Molecular Biology, 2017)
Peripheral T-cell lymphoma is the generic term of a group of heterogeneous disease in non-Hodgkin's lymphoma. To investigate the quantity of CD14+HLA-DR-/low MDSC and T cell subsets in peripheral blood of peripheral T cell lymphoma (PTCL) patients, and explore the biological functions of CD14+HLA-DR-/low MDSC in peripheral T-cell lymphoma. Flow cytometry was used to determine CD14+HLA-DR-/low MDSC and T cell subsets in peripheral blood of 33 peripheral T-cell lymphoma patients and 23 healthy cases; CD3 +T cells, CD14+HLA-DR-/low MDSC cells and HLA-DR+ cells were selected with magnetic activated cell sorting; Biotin-labeled micro magnetic beads (CD2 / CD3 / CD28) were used to stimulate amplification of CD3 + T cells, which were co-cultured and analyzed by flow cytometry for the effect of different concentrations of CD14+HLA-DR-/low MDSC on the proliferative activity of autologous CD3+ T cells. 1. CD14+HLA-DR-/low cells / CD14+ monocytes and CD4+ CD25+regulatory T cells Treg /CD4+Tlymphocytes were 3.28% (0.40% -17.74%) and 8.81% (0.76% -78.11 %) respectively, higher than the healthy control group with statistically significant difference (P <0.05);. 2. CD4+CD25+ Treg /CD4+Tlymphocyte and CD14+HLA-DR-/CD14+ monocytes in nucleated cells of lymphoma patients were 8.81% (0.76%-78.11%) and 3.28% (0.40% -17.74%) respectively, which was in positive correlation (correlation coefficient r = 0.510), with statistically significant difference (P = 0.002); 3. When the ratio of CD14+HLA-DR-/low and T cells was 1: 1, the proliferation inhibition of MDSC on autologous T cell is the strongest; after adding nor-NOHA, an ARG1 inhibitor, proliferation of T cells was recovered to 75.09 ± 5.18 %, IDO inhibitor 1-MT made the proliferation rate of T cells recovered to 84.05 ± 2.93%, and the proliferation rate of T cells was recovered to 97.80 ± 2.20% after combination of the IDO inhibitor and ARG1 inhibitor. CD14+HLA-DR-/lowMDSC inhibit the proliferation of T lymphocytes, which may be related ARG1 and IDO.